Aplikasi Penggunaan Silika dari Slag Nikel untuk Menurunkan Kadar Fosfat - Eko Andrian (SAINS : Jurnal Kimia & Pendidikan Kimia, 2021)
Research has been carried out on Reducing Phosphate Levels in Solutions Using Silica from Nickel Slag as an adsorbent. Nickel slag is industrial waste in the metal smelting process in the form of residue or waste in the form of lumps that have low quality because they are mixed with other materials that are difficult to separate. Nickel slag has a chemical composition of 41.47% silica, 30.44% ferric oxide and 2.58% alumina. This content allows the use of silica from nickel slag as an adsorbent to reduce phosphate levels in solution. This study aims to determine the optimum pH of the solution, the effect of mass variations and the effect of silica adsorbent contact time to reduce phosphate levels. The method used is quantitative analysis method. The results showed that silica absorbs phosphate at optimum pH 3 with an adsorption efficiency of 94.68%, the effect of the highest mass variation of absorption silica occurs at a mass variation of 0.05 grams with an adsorption efficiency of 94.68% and the highest contact time effect is at 15 minutes with an adsorption efficiency of 94.68%. Thuse silica can be used as an adsorbent to reduce phosphate levels.